Contact times in professional football before and during the SARS-CoV-2 pandemic: Tracking data from the German Bundesliga. Issue 3 (4th March 2023) - Szymski, Dominik; Weber, Hendrik; Anzer, Gabriel; Alt, Volker; Meyer, Tim; Gärtner, Barbara C.; Krutsch, Werner
ABSTRACT: The global SARS-CoV-2 pandemic led to a lockdown in team sports in March 2020. Because the risk of virus transmission seems to correlate with the duration of close contacts, data on contact times are necessary to assess the risk of virus transmission in sports. In this study, an optical tracking system was used to determine contact times between players of the two highest men's professional football leagues in Germany in the 2019–20 season and in the first half of the 2020–21 season. Contacts between players were defined as being within a two-metre radius during matches and were differentiated as either match-specific or non-match-specific. In total, 918 matches with 197, 087 contacts were analysed. The mean overall contact time of one-to-one situations of 36 s (SD: ± 66) before the lockdown was reduced to 30 s after the lockdown (SD: ± 60) ( p < 0.0001). In professional football, contacts between two players infrequently occur within a two-metre radius, averaging less than 35 s. Only 36 player pair contacts lasted for more than 15 min (0.00018%). The mean accumulated contact time per player with all others was 10.6 ± 6.9 min per match, with a decrease from 11.6 ± 7.0 min before the lockdown to 10.0 ± 6.6 min ( p < 0.0001) after lockdown in the season 2019-20. The SARS-CoV-2 pandemic has resulted in a reduction in match-specific contacts of 25%. It seems questionable if such short contacts in open-air sports may lead to considerable virus transmission.